A Study of Dimple Characteristics on Golf Ball Drag. (2016) - Chowdhury, Harun; Loganathan, Bavin; Wang, Yujie; Mustary, Israt; Alam, Firoz
Abstract: Dimples on the golf ball have significant effect on its aerodynamic properties as well as the flight trajectory. The aerodynamic of golf ball is still not fully understood in spite of a significant number of published data in the open literature. Most studies were conducted using the wind tunnel testing and Computational Fluid Dynamics (CFD) simulation. This paper examines the aerodynamic effect of dimple depth on golf balls. 3D printing technology was used to manufacture 11 balls with varied dimple depth. RMIT Aero Wind Tunnel was used to measure the drag forces over a range of wind speeds. It was found that the drag coefficient of golf ball varied significantly due to varied dimple geometry. The results indicate that the increase of the dimple depth ratio or surface roughness of the golf ball can shift the transition to a lower Reynolds number and increase the drag coefficient in transcritical regime. The results also established a positive linear correlation between relative roughness and drag coefficient.